CLINICAL AND LABORATORY ASSESSMENT OF GASTROINTESTINAL FUNCTION IN CHILDREN WITH ACUTE NEUROINFECTION - Markov, A.I. (The Ukrainian Scientific Medical Youth Journal, 2017)
Background. In cases of severe forms of infectious diseases, in addition to local inflammation, secondary lesions of the organs of the gastrointestinal tract may occur. We aimed to study the semiotics and epidemiology of gastrointestinal symptoms in children with acute neuroinfection.Material and methods. The study is observational, retrospective, type “case-control”. We analyzed cases of inpatient treatment of children aged 1 month to 18 years old with acute neuroinfections (meningitis, encephalitis and encephalomyelopolyneuropathy).Results and discussion. The study included 117 children with acute central nervous system infectious. Clinical symptoms of GI tract infection were observed in 83 (70.9%) children. Among revealed symptoms disorders of intestinal motility like constipation and diarrhea were prevalent. Manifestations of hepatobiliary system dysfunction included increased transaminase level (ALT, LF, GGTP) and/or ultrasound changes (enlargement, diffuse structural changes) and were observed in 39.1% of patients. Among the laboratory parameters, elevated ALT level was observed in 8.3% of patients, bilirubin was elevated in only one child, alkaline phosphatase was above the age norm of 11.8%, an increased GGTP above the age norm was observed in 31.3% of patients. The I-FABP biomarker level was elevated in 86.4% of patients, and L-FABP was elevated in all (100%) patients. Clinical manifestations of gastrointestinal dysfunc- tion (the presence of at least one of the gastrointestinal symptoms) had an inverse relationship with the child’s age (rpb = -0.19, p = 0.033), correlated with staying in ICU (OR = + 5.25 CI: 1.62 -16,97), artificial ventilation (OR = =+ 4,5 DI: 1,00-21,69) and level of I-FABP (rpb = 0,34, p = 0,019).Conclusions. Among gastrointestinal symptoms in children with acute neuroinfections, disorders of intestinal motility like constipation and diarrhea are most common. Hepatobiliary system dysfunction is mainly manifested by moderate changes in laboratory parameters. Biomarkers I- FABP and L-FABP are highly sensitive tests for the damage of the gastrointestinal tract and hepatobiliary system.